2016
DOI: 10.1016/j.jenvman.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two tools for ecosystem service assessments regarding water resources decisions

Abstract: We present a comparison of two ecohydrologic models commonly used for planning land management to assess the production of hydrologic ecosystem services: the Soil and Water Assessment Tool (SWAT) and the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) annual water yield model. We compare these two models at two distinct sites in the US: the Wildcat Creek Watershed in Indiana and the Upper Upatoi Creek Watershed in Georgia. The InVEST and SWAT models provide similar estimates of the spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(41 citation statements)
references
References 40 publications
1
39
0
1
Order By: Relevance
“…Preliminary runs of these models indicated that transpiration was much lower than expected. As pointed out by [45], this was due to a default operation practice in SWAT that kills and harvests the crops or forests every year. Such a forestry operation was not expected in our watersheds, and thus was removed, and the initial settings for tree growth for both types of simulations (five-year and annual) were modified accordingly.…”
Section: Swat Simulationsmentioning
confidence: 99%
“…Preliminary runs of these models indicated that transpiration was much lower than expected. As pointed out by [45], this was due to a default operation practice in SWAT that kills and harvests the crops or forests every year. Such a forestry operation was not expected in our watersheds, and thus was removed, and the initial settings for tree growth for both types of simulations (five-year and annual) were modified accordingly.…”
Section: Swat Simulationsmentioning
confidence: 99%
“…Nevertheless, forests with deep roots and low direct runoff provide the largest part of the water supply, and forest water yields can be used to determine the amount of total supply [27]. For the calculation of the water yield, various methods suggested by the previous studies included factors such as land use, forest species, age-class, precipitation, amount of evapotranspiration, porous ratio and depth of root [28,29].…”
Section: The Concept Of Forest Water Supply and Yieldmentioning
confidence: 99%
“…Since a lot of information is missing from reported sites to make this comparison effective, some studies used numerical simulations to evaluate the effect of each parameter on BMP system performance. Some of the numerical simulation studies include the Hydrological Simulation Program-Fortran (HSPF) [3,14], the Soil and Water Assessment Tool (SWAT) [15,16], the Long-Term Hydrologic Impact Assessment-Low Impact Development (L-THIA-LID) [17][18][19], and the Storm Water Management Model (SWMM) [20][21][22][23][24]. This paper seeks to explore BMP performance deterioration due to sediment accumulation using field and numerical simulations.…”
Section: Soil Type and Sedimentationmentioning
confidence: 99%